2019
DOI: 10.1139/facets-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns in deep acoustic backscatter layers near vent plumes in the northeastern Pacific Ocean

Abstract: We used moored 75 kHz acoustic Doppler current profilers (ADCPs) to examine seasonal cycles in zooplankton deep scattering layers (DSLs) observed below 1300 m depth at Endeavour Ridge hydrothermal vents. DSLs are present year-round in the lower water column near vent plumes. Temporal variations suggest passive, flow-induced displacements superimposed on migratory movements. Although the strongest DSLs are shallower than the neutrally buoyant plumes (1900–2100 m), anomalies also occur at and below plume depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…These vertical water mass motions, with apparent semi-diurnal frequency and with amplitude of over 200 m at the start of the recorded interval but diminishing towards the end of it, are likely associated with upslope moving internal tidal waves as described by Hosegood et al (2004) and Hall et al (2017). The zooplankton/nekton in the aphotic zone (1000-1400 m) of the Whittard Canyon, if indeed that is what was producing the observed backscatter patterns, therefore seems not to be actively migrating but passively following the internal tidal motions, as was also inferred in studies by Ibáñez-Tejero et al (2018) and Burd and Thomson (2019). Unfortunately, in our present dataset from the Whittard Canyon we have no direct observational evidence, from either an underwater camera or plankton net hauls, to verify the nature of the particles producing the low-frequency acoustic backscatter signal.…”
Section: Bottom Boundary Layer Spm Dynamics Observed With Obs and 75 ...supporting
confidence: 69%
“…These vertical water mass motions, with apparent semi-diurnal frequency and with amplitude of over 200 m at the start of the recorded interval but diminishing towards the end of it, are likely associated with upslope moving internal tidal waves as described by Hosegood et al (2004) and Hall et al (2017). The zooplankton/nekton in the aphotic zone (1000-1400 m) of the Whittard Canyon, if indeed that is what was producing the observed backscatter patterns, therefore seems not to be actively migrating but passively following the internal tidal motions, as was also inferred in studies by Ibáñez-Tejero et al (2018) and Burd and Thomson (2019). Unfortunately, in our present dataset from the Whittard Canyon we have no direct observational evidence, from either an underwater camera or plankton net hauls, to verify the nature of the particles producing the low-frequency acoustic backscatter signal.…”
Section: Bottom Boundary Layer Spm Dynamics Observed With Obs and 75 ...supporting
confidence: 69%
“…Rona et al (2006) observed changes in plume bending direction over a 24 h interval that were consistent with a semi-diurnal tidal cycle in bottom current direction and speed (Figure 2 shows a more recent example of a 24 h plume imaging record). Other studies (Burd and Thomson, 2019) have identified a neutrally buoyant plume between 1900-2,100 m depth that varies in depth during the late summer and fall, suggesting a change in the balance between plume rise rate and bottom current speeds.…”
Section: Motivationmentioning
confidence: 88%
“…Near-surface currents in the NE Pacific are expected to flow to the east and northeast due to the Eastward North Pacific Current (Strub and James, 2002a;Strub and James, 2002b). However, due to the complex topography associated with the Juan de Fuca Ridge, the background tides and currents of the open ocean are likely modified (Burd and Thomson, 2019). In particular, the interaction of semidiurnal tides with the abrupt ridge topography is expected to generate passive vertical displacements of up to 100 m based on earlier current meter measurements in the area (Mihaly et al, 1998) and on numerical simulations in similar settings (Xu and Lavelle 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above the neutrally buoyant plume, towed nets along with acoustical methods identified a deep scattering layer associated with the aggregation of zooplankton (e.g., Burd and Thomson, 2012). This deep scattering layer has been shown to have a complex seasonal and higher frequency (20-40d) variability likely due to a combination of both ontogenetic migration and dynamic advective processes (Burd and Thomson, 2019). In the rift valley of the northern MAR, the compilation of different in situ data acquired by CTD-LADCP casts and mooring deployments during repeated visits (Lahaye et al, 2019), combined with modeling studies (Vic et al, 2018b) has revealed consistent north-eastward along-valley currents below 2000 m at sub-inertial time scales.…”
Section: Water Column: Deep Circulation Fluid Dispersal and Connectivitymentioning
confidence: 99%